When I dance - Berry, James, 1924-2017.; Boyce, Sonia (London : Hamish Hamilton, 1988)
A collection of fifty-nine poems for young adults celebrating life in inner-city Britain and in the rural Caribbean.
NLJCols20082021
Keywords: Young adult poetry, Jamaican; West Indians -- Great Britain -- Poetry; West Indians; Young adult poetry, Jamaican; Jamaican poetry; Caribbean Area -- Poetry; Caribbean Area; Great Britain; Poetry in English, 1945- - Texts; Poetry